Diskretna matematika - Tepeh, Aleksandra; Škrekovski, Riste (2018)
Discrete Mathematics. This textbook is designed for higher education students of computer sci- ence and information technologies. It presents an introduction to selected topics in discrete mathematics needed for understanding and solving problems that arise in computer science. Besides propositional logic, relations and graph theory the textbook contains a chapter on geometric vectors and a chapter on matrices. Together with theoretical background many examples are given, as well as exercises together with complete solutions.
Keywords: propositional calculus; matrix; vector; relation; graph